Assessing livelihood impacts of cage based fish fingerlings production on Adivasi households in north-east and north-west Bangladesh - Gupta, N; Haque, MM (Journal of the Bangladesh Agricultural University, 2012)
In Bangladesh, Adivasi, the indigenous people are of the poorest sections of the society due to their vulnerable livelihoods with lack of resources. Cage based fish fingerling production (CBFFP) was promoted with Adivasi households in the north-east and north-west regions of Bangladesh. A structured questionnaire based survey was conducted with a sample size of 150 CBFFP adopting households to assess the livelihood impacts of CBFFP on the Adivasi households. Geographically, the study represents Sherpur and Netrakona districts from north-east and Dinajpur, Rangpur, and Joypurhat districts from north-west regions of Bangladesh. In terms of socio-economic characteristics, the average household size of Adivasi households was 4.21± 1.28 with day labour (40%) based primary occupation. Majority (64%) of households heads were found illiterate and the remaining with low level education attainment. Most of the Adivasi households depended on a single persons (household head) income. The average size of ponds in which the cages were set was about 1.2±1.4 hectare with the depth of 1.5-3 m. The cage provided with Adivasi farmer was of 1 m3 in size and made of locally available materials, mainly bamboo made frame, net and plastic bottles as floats. The average cost of a cage construction was about BDT 400±85.2 (USD 5.71±1.2). The fry of tilapia (Oreochromis niloticus), silver carp (Hypophthalmichthys molitrix), rui (Labeo rohita), mrigal (Cirrhinus cirrhosus), bighead carp (Aristichthys nobilis), common carp (Cyprinus carpio), Thai sarpunti (Barbonymus gonionotus) were stocked in the cages for fingerling production. The average stocking density was about 875±507 fry/cage (about 3.4cm in length). In average, fingerling production cost was about BDT 268±129.2/cage (USD 3.83±1.8/cage) and selling value was about BDT 431±509.1/cage (USD 6.16±7.2/cage). The major impacts of CBFFP include increased household level income (1.7%), use of this income to buy livestock for rearing further. Moreover, CBFFP impacted positively on other aspects of livelihoods such as purchasing food in lean period, saving money and paying credit. The large size fingerlings produced in the cages were used as food fish for household level consumption. The main constrains of Adivasi households to adopt CBFFP were poaching of fish from cages and variable access to ponds for cage installation. DOI: http://dx.doi.org/10.3329/jbau.v9i2.11047 J. Bangladesh Agril. Univ. 9(2): 319326, 2011